PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS DAN KOMUNIKASI KERJA TERHADAP KEPUASAN KERJA UPTD PUSKESMAS WIYUNG - Ernawati; Muhammad Husain (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to determine the influence of democratic leadership style and work communication on employee job satisfaction at UPTD Puskesmas Wiyung. The background of this research is the importance of participative leadership and effective communication in creating a supportive work atmosphere that enhances job satisfaction. The research method used is a quantitative approach with a Likert scale questionnaire as the instrument and multiple linear regression analysis as the technique. The population of this study consisted of all employees at UPTD Puskesmas Wiyung with a sample of 63 respondents. The results show that the democratic leadership style has a positive and significant effect on job satisfaction. Likewise, work communication also has a positive and significant effect on job satisfaction. Simultaneously, both variables significantly influence job satisfaction. The conclusion is that the application of a democratic leadership style and effective work communication can improve employee job satisfaction.